Frequency of Delayed Onset of Traumatic Extradural Hematoma in Patients Presenting with Head Injuries - Faizyab Ahmed, Irum Bukhari, Saleem Shah, Sajjad Mehmood, Nadia Banaras, Shahjahan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess the frequency of delayed traumatic extradural hematoma in patients presenting with head injuries in emergency of a tertiary care hospital. Materials and Methods: In this case series a total 125 patients who presented with head injury were included. All patients underwent assessment on Glasgow Coma Scale (GCS) and score was noted at baseline. Then patients were managed according to hospital protocol. After procedure, patients were shifted to post-surgical ward and were followed-up for 5 days. After 3 and 5 days, CT scan was done to assess presence or absence of extradural hematoma. Results: Mean age of patients in this study was 34.53±10.82 years. In this study 86 (68.8%) patients were male and 39 (31.2%) patients were female. In this study, 20 (16%) patients had delayed onset of Traumatic extradural hematoma in patients presenting with head injuries. DEDH was diagnosed in 45% patients having age 20-30 years, in 35% patients having age 31-40 years and in 20% patients having age >40 years. DEDH was diagnosed in 13 (65%) patients having baseline GCS 11-12, in 20% patients having GCS 8-10, in 15% patients having GCS 13-14. Conclusion: In this study frequency of delayed onset of Traumatic extradural hematoma in patients presenting with head injuries was 16%. Highest frequency (45%) was seen in the younger age group; 20-30 years, among male (65%) patients and those having baseline GCS in the range 11-12 (65%). Keywords: Traumatic extradural hematoma, delayed onset, head injury.